Instrumenty marketingu mix wykorzystywane przez wybrany podmiot agrobiznesu w sytuacji nasilającej się konkurencji na rynku roślin ozdobnych - Szymańska, Joanna (Instruments of Marketing Mix Used by Chosen Agribusiness Subjects in the Situation of Growing Competition on the Market of Flowers and Plants, 2006)
The paper presents a situation on the market of flowers and plants in Poland. It shows reasons of growing competitions on this market and presents the idea of marketing mix chosen by one of the subjects on this market as a way of getting competitive advantage. The paper analyses marketing instruments (product, price, distribution, promotion) used by the company. It shows the author suggestions about a possible improvement in its competitiveness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 411-417